2017
DOI: 10.1002/pmic.201700302
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Plasma Membrane Glycoproteins Specific to Human Glioblastoma Multiforme Cells Using Lectin Arrays and LC‐MS/MS

Abstract: Glioblastoma, also known as glioblastoma multiforme (GBM), is the most malignant type of brain cancer and has poor prognosis with a median survival of less than one year. While the structural changes of tumor cell surface carbohydrates are known to be associated with invasive behavior of tumor cells, the cell surface glycoproteins to differentiate the low-and high-grade glioma cells can be potential diagnostic markers and therapeutic targets for GBMs. In the present study, lectin arrays consisting of eight lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…High-grade glioma cells showed overexpression of several sialyl-and fucosyltransferases involved in the biosynthesis of Lewis glycans and the high expression of SLe x could be attributed to the expression of FUT7/11 and ST3GAL3. Similar results were recently reported by Park and colleagues, they found that the high-grade glioma cell line T98G expressed higher levels of α1,2 fucose and α2,3 sialic acid in comparison with the low-grade glioma cell line Hs683 [36]. In the same line, a microarray analysis of glyco-gene expression in human glioblastomas carried out by Kroes reported the identification of glycosyltransferases gene expression profiles able to classify cancer types employing expression data taken from cancer patient samples in TCGA and, remarkably, ST3GAL3 gene was found to be highly overexpressed in GBM [38].…”
Section: Discussionsupporting
confidence: 91%
“…High-grade glioma cells showed overexpression of several sialyl-and fucosyltransferases involved in the biosynthesis of Lewis glycans and the high expression of SLe x could be attributed to the expression of FUT7/11 and ST3GAL3. Similar results were recently reported by Park and colleagues, they found that the high-grade glioma cell line T98G expressed higher levels of α1,2 fucose and α2,3 sialic acid in comparison with the low-grade glioma cell line Hs683 [36]. In the same line, a microarray analysis of glyco-gene expression in human glioblastomas carried out by Kroes reported the identification of glycosyltransferases gene expression profiles able to classify cancer types employing expression data taken from cancer patient samples in TCGA and, remarkably, ST3GAL3 gene was found to be highly overexpressed in GBM [38].…”
Section: Discussionsupporting
confidence: 91%
“…The main differentially expressed protein domains in GBM plasma extracellular vesicles include members of complement and coagulation cascade and regulators of iron metabolism. The role of these proteins has been already described in GBM biology, thus making these targets extremely interesting for extracellular vesicle-based biomarker development (46)(47)(48)(49)(50)(51)(52)(53). We demonstrate that the clinical correlation of plasma extracellular vesicles is with the presence of the tumor.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, relative quantitative analysis was also performed for S1M, S1N, S1E, S2M, and S3M. A label‐free quantitative method approach using spectral counting and normalized spectral abundance factor (NSAF) 50 was used to calculate the relative abundance of each identified intact N‐glycopeptide: RelativeAbundancek=()SpGPSMsknormali=1NSpGPSMsi. The total number of GPSMs of each glycopeptide (SpGPSMs, defined by the peptide sequence, N‐glycosite and N‐glycan, composition) was divided by the sum of all the GPSMs. The relative quantitative results of all the datasets are listed in Sheets 1–5 of Table S3 (supporting information) .…”
Section: Resultsmentioning
confidence: 99%